FOSTERING THE STUDENTS’ SPEAKING ABILITY THROUGH COMMUNICATIVE APPROACH OF PARTICIPATION POINT SYSTEM - Apriana; Anggraini, Lesi (Esteem Journal of English Education Study Programme, 2025)
The objective of this study was to investigate how the implementation of a communicative participation point system could enhance students' speaking abilities. Specifically, the research aimed to determine whether the use of the participation point system influenced students' grades and how students perceived its role in developing their English-speaking skills. The study focused on both the learners' perceptions and their performance scores. A sample of 36 students was selected from a total of 150 12th-grade students at SMA Negeri 4 Palembang. Utilizing a mixed-method approach with an explanatory sequential design, quantitative and qualitative data were collected in two phases, with each phase informing the other. The findings revealed that the t-value (4.846) exceeded the t-table value (1.680), confirming that the alternative hypothesis (Ha) was valid. This indicates that the application of the communicative participation point system had a significant impact on students' speaking performance and scores.